2022
DOI: 10.1055/a-1939-4031
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Single Giant Renal Cyst in a Newborn with Drainage and Sclerotherapy

Abstract: Simple renal cysts are a scare entity in pediatric patients and their etiology is unknown in most cases. Usually, they are monitored with ultrasound and regular follow up of renal function. Surgical treatment is rarely indicated. We report the case of a newborn with a single giant renal cyst that could be treated successfully with drainage and sclerotherapy. Single giant renal cysts require careful investigation and monitoring. In cysts without communication to the pelvico-caliceal system, sclerotherapy by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(47 reference statements)
0
2
0
Order By: Relevance
“… 13 Additionally, Koenig et al presented a newborn with a giant renal cyst treated successfully with sclerosing agent treatment, which was treated successfully. 6 Following a single session of alcohol treatment into the cyst in our patient, the cyst size shrank. A 2-year follow-up revealed that the cyst had entirely vanished.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“… 13 Additionally, Koenig et al presented a newborn with a giant renal cyst treated successfully with sclerosing agent treatment, which was treated successfully. 6 Following a single session of alcohol treatment into the cyst in our patient, the cyst size shrank. A 2-year follow-up revealed that the cyst had entirely vanished.…”
Section: Discussionmentioning
confidence: 64%
“…Treatment options are percutaneous drainage under sonographic guidance with or without sclerotherapy and a surgical approach either open or laparoscopically. 6 In this report, we discuss the pediatric case of a solitary giant renal cyst and its therapeutic approach. Verbal and written informed consent was obtained from the patient who agreed to take part in the study.…”
Section: Introductionmentioning
confidence: 99%